Impact of Cluster Front Line Demonstrations on performance of Chickpea Crop in Western Rajasthan - Sumitra Devi Bamboriya; Arjun Singh Jat; Shanti Devi Bamboriya (Annals of Agricultural Research, 2023)
The cluster frontline demonstrations (CFLDs) on chickpea was conducted by Krishi Vigyan Kendra, Maulasar at Nawan and Makrana tehsil of Nagaur district during the Rabi season of 2018-19 to 2020-21. The results revealed that improved varieties, seed and soil treatment, nutrient and weed management and plant protection measures recorded average higher yield (1.77 t/ha) as compared to local check (1.39 t/ha). The same was found in case of net returns, which was Rs. 67183/ha for demonstrated plot and Rs.50470/ha for local check, respectively. Benefits cost ratio was recorded to be higher under demonstration (3.20) against local check (2.79) during the years of experimentation. It can be concluded that the pulses production could be enhanced by encouraging the farmers through adoption of recommended technologies which were followed in the CFLDs.